2022
DOI: 10.1186/s12877-022-03360-5
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and physical activity of older adults during the COVID-19 pandemic: a cross-sectional study in a northern Japanese City

Abstract: Background Little is known of whether Internet use is associated with physical activity among socially isolated older adults during the coronavirus disease 2019 (COVID-19) pandemic. This study investigated the association between Internet use and physical activity, and whether this association differs depending on social isolation among community-dwelling Japanese older adults. Methods A cross-sectional study was conducted with 1048 community-dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Before the COVID-19 outbreak, previous studies [71] reported that mHealth and eHealth interventions based on the use of smartphones or tablet PC use increase PAEXP in older adults. In addition, there are studies showing that the use of ICT devices was significantly associated with PAEXP during COVID-19 confinement [56,57]. Our results support the results of these previous studies [56,57] and simultaneously extend the validity of results showing the factors influencing PAEXP during the COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Before the COVID-19 outbreak, previous studies [71] reported that mHealth and eHealth interventions based on the use of smartphones or tablet PC use increase PAEXP in older adults. In addition, there are studies showing that the use of ICT devices was significantly associated with PAEXP during COVID-19 confinement [56,57]. Our results support the results of these previous studies [56,57] and simultaneously extend the validity of results showing the factors influencing PAEXP during the COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there are studies showing that the use of ICT devices was significantly associated with PAEXP during COVID-19 confinement [56,57]. Our results support the results of these previous studies [56,57] and simultaneously extend the validity of results showing the factors influencing PAEXP during the COVID-19 lockdown. Therefore, in order to maintain and promote the PAEXP of older adults, it is necessary to continue to pay attention to the application of ICT devices such as smartphones or tablet PCs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The recent COVID-19 pandemic has shown that face-to-face exercise is not always feasible, highlighting the relevance of alternative strategies when mobility restrictions or accessibility difficulties exist [101]. Home-based exercise sessions have increased in popularity during the pandemic [102][103][104]. In this sense, the development of the mobile application used by the unsupervised exercise groups in the present study might provide a tool with scientific validity to all those older adults who want to start an exercise program from home.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the association of Internet use and residents’ physical exercise has gradually become a major research topic [ 28 , 29 , 30 , 31 , 32 ]. Some scholars argue that Internet use encourages physical exercise among older adults by increasing individuals’ access to information [ 31 ], facilitating community communication and enhancing the knowledge of exercise and sports. For example, Wang et al (2021) found that Internet use had a significant impact on increasing physical exercise by using the 2017 China General Social Survey data [ 33 ].…”
Section: Introductionmentioning
confidence: 99%